Optimization of Roll Die Cutting Machine Utilization in the Production Fold Carton Packaging - Wicaksono, Dimas Priyo; Imam, Saeful; Yamin, Iqbal; Suharto, Nurlita Pratiwi; Sinur, Valeri Vela (Journal of Engineering, Technology, and Applied Science (JETAS), 2026)
Folded carton packaging is commonly used in various industries due to its lightweight, flexible, and environmentally friendly properties. Roll die cutting machines are the primary technology used in mass production because they can achieve cutting Accuracy of up to 99% with only 1,2% material waste at optimal parameters (pressure of 5 bar, speed of 20 m/min, blade sharpness of 0.1 µm). Therefore, this study uses an experimental method to optimize cutting parameters by varying pressure (3-7 bar), speed (10-30 m/min), and blade sharpness (0.1-0.5 µm). The research results show that the use of a blunt blade (0.5 µm) at high pressure (7 bar) can reduce Accuracy by up to 85% and increase Waste by up to 10%. Comparison with flatbed cutting machines reveals the superiority of roll die cutting in terms of production speed (three times faster) and precision (four % higher), despite requiring 50% higher maintenance expenses. The implementation of these optimal parameters in industry is projected to increase productivity by up to 30% while reducing material waste by up to 40%, provided that routine blade maintenance is performed every 5,000 cutting cycles. These findings offer significant technical recommendations for improving the efficiency of folding carton packaging production.